Tracer Study Online Universitas Bung Hatta - Suryani, Karmila (Jurnal EDik Informatika, 2015)
This research aim to design systems detection of graduated that it was need  by stakeholders and very according to BAN-PT rules. This Program was design to use PHP and Mysql by using CMS Bootstrap. There are four actor that have authoritative, i.e; colegiate, stakeholders, head of university, and admin. Scheme of system use method of waterfall, with stages;steps which consist of process of analysis, design, coding, testing, and maintenance. In this time scheme have come up with small scale phase and expert. The big scale test will be conducted at August 2015 after getting permission of head univefrsitas and take this program in Web of Bung Hatta university.